Shifting Frontiers: The Making of Matopiba in Brazil and Global Redirected Land Use and Control Change - Calmon, Daniela (Journal of Peasant Studies, 2022)
Abstract: There are not fixed conditions that make potential agricultural frontiers attractive to capital: different spaces and strategies are chosen in relation to previous failed experiments, including those strongly contested by social movements. Socio-environmental contestations can also inadvertently result in negative spillovers, or a kind of indirect land use change. I propose a concept of redirected land use and control change for cases with strategic adaptations by promoters of frontiers. I suggest three dimensions of adaptations – across spaces, political-administrative regimes and in forms of land appropriation – to apprehend the multi-scale politics of land grabbing, through the case of Matopiba in Brazil.
Number: 2